Metode Pembelajaran Syekh Al-Zarnuji Dalam Perspektif Multiple Intelligences Howard Gardner - Dimyati Sajari; Nila Durri Al Maqrizi (CV. ULIL ALBAB CORP, 2024)
This study aims to analyze the learning methods of Sheikh Al-Zarnuji and relate them to the theory of multiple intelligences developed by Howard Gardner. Sheikh Al-Zarnuji, a 13th century Muslim scholar, is known for his work 'Ta'lim al-Muta'allim', which focuses on ethics and effective learning methods. Through literature review and comparative analysis, this research explores the key principles proposed by Al-Zarnuji, such as the importance of intention, consistent effort, and the role of the teacher in education. The findings show that many of the methods and principles proposed by Al-Zarnuji are consistent with Gardner's concept of multiple intelligences, which emphasizes that each individual possesses a variety of different types of intelligence, such as linguistic, logical-mathematical, musical, bodily, spatial, interpersonal, intrapersonal, and naturalistic. The findings suggest that Al-Zarnuji's approach to learning is not only relevant in its historical context, but can also be integrated with modern educational theories to create more inclusive and effective learning strategies. This research makes an important contribution to understanding how traditional learning methods can be applied in contemporary educational contexts, taking into account the different intelligences possessed by learners.